2011
DOI: 10.1245/s10434-011-2122-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Sentinel Node Micrometastases in Patients with Clinical N0 Gastric Carcinoma with Real-time Multiplex Reverse Transcription-Polymerase Chain Reaction Assay

Abstract: The real-time multiplex RT-PCR assay is a useful tool for the detection of MM in SNs and NSNs in patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 28 publications
0
41
0
1
Order By: Relevance
“…It was reported that 24 % of patients with SN metastasis diagnosed by permanent sections could not be identified by frozen sections during the operation in the trial conducted by the Japan Society of Sentinel Node Navigation Surgery [7]. Different methods such as multistep level section, immunohistochemistry [23,24], reverse transcription PCR (RT-PCR) [25][26][27][28], and the one-step nucleic acid amplification assay [29] have been developed to reduce the falsenegative rate by an additional diagnosis for micrometastasis in SNs. Micrometastases were detected in four of 35 patients (11 %), and six of 1,028 nodes (0.58 %) without metastasis diagnosed by permanent section, using a combined technique of complete serial sectioning and immunohistochemistry [23].…”
Section: Intraoperative Diagnosis Of Snsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that 24 % of patients with SN metastasis diagnosed by permanent sections could not be identified by frozen sections during the operation in the trial conducted by the Japan Society of Sentinel Node Navigation Surgery [7]. Different methods such as multistep level section, immunohistochemistry [23,24], reverse transcription PCR (RT-PCR) [25][26][27][28], and the one-step nucleic acid amplification assay [29] have been developed to reduce the falsenegative rate by an additional diagnosis for micrometastasis in SNs. Micrometastases were detected in four of 35 patients (11 %), and six of 1,028 nodes (0.58 %) without metastasis diagnosed by permanent section, using a combined technique of complete serial sectioning and immunohistochemistry [23].…”
Section: Intraoperative Diagnosis Of Snsmentioning
confidence: 99%
“…Micrometastases were detected in four of 35 patients (11 %), and six of 1,028 nodes (0.58 %) without metastasis diagnosed by permanent section, using a combined technique of complete serial sectioning and immunohistochemistry [23]. Shimizu et al [28] established a highly sensitive real-time RT-PCR system to detect the messenger RNA (mRNA) of cytokeratin 19, cytokeratin 20, and carcinoembryonic antigen, demonstrating that 27 % of the patients had negative pathological but positive RT-PCR findings. In seven patients (6.8 %), SNs were negative but non-SNs were positive on RT-PCR in that report.…”
Section: Intraoperative Diagnosis Of Snsmentioning
confidence: 99%
See 1 more Smart Citation
“…These actions can cause inaccurate tumor staging and lead to improper therapeutic management (Gu, 2002;Coello, 2004;Imoto, 2006;Broglie, 2011;Rahbari, 2012). Many studies have developed methods for detecting occult tumor cells or DNA, including serial section staining, immunohistochemistry, PCR and RT-PCR-based methods (Tsavellas, 2001;Riethdorf, 2008;Wada, 2008;Shimizu, 2012); however, their conclusions have been less satisfactory. In this study, we aimed to determine whether LINE-1 and Alu methylation measurements are effective biomarkers for the detection of occult metastatic HNSCC and whether these measurements can provide a supportive method for diagnosing nodal metastases from HNSCC as an alternative to routine pathological examination.…”
Section: Line-1 and Alu Methylation Patterns In Lymph Node Metastasesmentioning
confidence: 99%
“…11,12) Even when false-negative cases occur due to technical problems of SN identification and overlooked findings of intraoperative rapid cytodiagnosis, actual lymph node metastasis is present in the SN basin and can be frequently identified. 13) In patients with clear SN metastasis, since the possibility that metastasis is also present outside the SN basin cannot be excluded, standard resection and dissection are necessary at present.…”
Section: ) Gastric Cancermentioning
confidence: 99%